2014
DOI: 10.3346/jkms.2014.29.9.1247
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Prevalence of Gallbladder Polyps in Korea

Abstract: Only a few studies have evaluated the population-adjusted prevalence of gallbladder polyps (GBP). This study aimed to evaluate the changes in GBP prevalence and risk factors at a single health screening center in Korea from 2002 to 2012. Of 48,591 adults who underwent health screening between 2002 and 2012, 14,250 age- and gender-matched subjects were randomly selected to evaluate prevalence. Risk factors were analyzed between the GBP-positive and GBP-negative groups during 2002-2004 (Period A) and 2010-2012 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 22 publications
3
22
5
1
Order By: Relevance
“…A Korean study in 1999, which evaluated patients who underwent health screening examinations, reported the overall prevalence to be 2.94% (3.63% in men, 2.09% in women) 12. Another Korean study in 2012 reported an 8.5% prevalence 13. In our study, the prevalence rate was 9.96%, which was higher than previously reported in Korea.…”
Section: Discussioncontrasting
confidence: 80%
“…A Korean study in 1999, which evaluated patients who underwent health screening examinations, reported the overall prevalence to be 2.94% (3.63% in men, 2.09% in women) 12. Another Korean study in 2012 reported an 8.5% prevalence 13. In our study, the prevalence rate was 9.96%, which was higher than previously reported in Korea.…”
Section: Discussioncontrasting
confidence: 80%
“…1,[6][7][8] GBPs prevalence is increasing among people who have increased age, male gender, hypertension, diabetes, hepatitis C infection, impaired fasting glycemia and obese. 9 The incidence is either equal or close in both genders. 4,5 Although polypoid lesions are seen in all ages, they are more common in individuals that are over 40 years old.…”
Section: Demographic Findingsmentioning
confidence: 99%
“…We also found that the frequency of gallbladder polyps in patients aged ≥50 yr was lower than that in patients aged <50 yr (7.4% vs. 8.3%). This finding was not unexpected because a large Korean study showed a peak in the prevalence of gallbladder polyps in males 30-39 yr of age and in females 40-49 yr age ( 27 ). In addition, CRNs were significantly more prevalent in patients with than in those without gallbladder polyps in the age ≥50 yr group (47.0% vs. 38.1%) but not in the age <50 yr group.…”
Section: Discussionmentioning
confidence: 73%
“…Two case-control studies from Korea suggested that metabolic syndrome contributes to the development of gallbladder polyps ( 14 26 ). In another large Korean study, in which 14,250 individuals were evaluated, a possible influence of obesity and hyperlipidemia on the risk of developing gallbladder polyps was determined ( 27 ). A previous study from Japan also reported that patients with gallbladder polyps were more obese than patients in the control group ( 28 ).…”
Section: Discussionmentioning
confidence: 99%